1995
DOI: 10.1159/000168889
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure in Patients following Bone Marrow Transplantation: Prevalence, Risk Factors and Outcome

Abstract: To assess the prevalence, risk factors, clinical causes and outcome of acute renal failure (ARF) following bone marrow transplantation (BMT), a retrospective analysis of 275 patients was undertaken. ARF was diagnosed in 72 patients (26%) and occurred in 81.9% within the first month. The three main clinical causes were multifactorial (36%), nephrotoxic (29%), and veno-occlusive disease of the liver (VOD) 15%. The prevalence was higher in allogeneic BMT (36%) than in autologous BMT (6.5%). Risk factors related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 19 publications
6
85
1
Order By: Relevance
“…[8][9][10][11][12] Both myeloablative and non-myeloablative regimens have been associated with AKI, although its severity has been reported to be higher in the myeloablative HCT setting. 13 Myeloablative conditioning, hepatic VOD, 14 cis-platinum II nephrotoxicity, 15 acute GVHD, 16 amphotericin administration, admission to intensive care unit, 14 CMV reactivation, 16 diabetes melitus and elevated baseline GFR 17 have been described as risk factors for AKI in both myeloablative and reduced intensity HCT. In our study, 30.2% of patients with AKI developed CKD at 6.5 months post-transplant, ranging from 3 to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Both myeloablative and non-myeloablative regimens have been associated with AKI, although its severity has been reported to be higher in the myeloablative HCT setting. 13 Myeloablative conditioning, hepatic VOD, 14 cis-platinum II nephrotoxicity, 15 acute GVHD, 16 amphotericin administration, admission to intensive care unit, 14 CMV reactivation, 16 diabetes melitus and elevated baseline GFR 17 have been described as risk factors for AKI in both myeloablative and reduced intensity HCT. In our study, 30.2% of patients with AKI developed CKD at 6.5 months post-transplant, ranging from 3 to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality from acute renal insufficiency was 46%, the dialyzed group having the highest mortality (88%). 7 In a prospective study of 64 adult BMT recipients, 64% of the patients developed acute renal insufficiency, ie at least doubling of pre-BMT serum creatinine concentration. 8 In our study a high pre-BMT serum creatinine, transplantation with a non-HLA-identical related or matched unrelated donor compared to a HLA-identical sibling were risk factors for the development of acute renal insufficiency in the first 3 months after BMT.…”
Section: Acute Renal Insufficiencymentioning
confidence: 99%
“…4 In another study in adults only, veno-occlusive disease and an age older than 25 years were found to be risk factors related to the development of acute renal insufficiency. 7 Besides the obvious reasons for acute renal insufficiency following BMT such as reduced renal reserve after intensive chemotherapy and the direct effect of nephrotoxic medication, the causes of renal impairment following BMT are thought to be hemodynamic in origin. In support of this assumption are the occurrence of acute renal insufficiency after septicemia (hypotension), veno-occlusive disease (hepato-renal syndrome), amphotericin B administration (renal vasoconstriction) and a high serum urea/creatinine ratio consistent with prerenal insufficiency in adult studies.…”
Section: Acute Renal Insufficiencymentioning
confidence: 99%
“…It Four patients developed acute renal failure (ARF). ARF was defined, as previously described, 25 by at least a doubis noteworthy that 11 out of these patients were older than 50. No toxic deaths occurred among the 40 patients ling of baseline creatinine, assuming levels higher than 177 mmol/l (2 mg/dl).…”
Section: Patientsmentioning
confidence: 99%